ANALISIS KELAYAKAN FINANSIAL USAHATANI KAKAO DI KECAMATAN BULOK KABUPATEN TANGGAMUS - Maria Christina Pasaribu; Fembriarti Erry Prasmatiwi; Ktut Murniati (Lampung University, 2016)
The aims of this research are to analyze the financial feasibility and the sensitivity of cocoa monoculture farming and cocoa inter-cropping. This research was conducted in March-May 2016inpurposivelyselected Bulok District, Tanggamus Regency. The samples of theresearch were30 farmers selected randomly. Research data wer analyzed by using financial feasibility analysis method and sensitivity analysis. The results showed that cocoa monoculture and intercropping farming were financially profitable and feasible to be developed. The value of Net B/C and Gross B/C were bigger than 1. The value of NPV was bigger than 0 and IRR of cocoa farming was greater than 9% as the used interest rate. The Pay Period analysis of the cocoa farming system showed thatthe initial cash outflow of investment could be recovered less than 25 years. The feasibility value showed that cocoa intercropping farming was better thancocoa monoculture farming.The changes of sensitivity analysis showed that the production cost increase was 7.26%, the production price decrease was 22% and theproduction quantity decrease was 14%. The results of sensitivity analysis showed that cocoa monoculture farming was more sensitive than cocoa intercropping farming. Key words: cocoa, feasibility, financial, intercropping, sensitivity